Cost-effectiveness of 64-slice CT angiography compared to conventional coronary angiography based on a coverage with evidence development study in Ontario. (October 2013) - Goeree, Ron; Blackhouse, Gord; Bowen, James M; O'Reilly, Daria; Sutherland, Simone; Hopkins, Robert; Chow, Benjamin; Freeman, Michael; Provost, Yves; Dennie, Carole; Cohen, Eric; Marcuzzi, Dan; et al.
Conventional coronary angiography (CCA) is the standard diagnostic for coronary artery disease (CAD), but multi-detector computed tomography coronary angiography (CTCA) is a non-invasive alternative. Methods: A multi-center coverage with evidence development study was undertaken and combined with an economic model to estimate the cost–effectiveness of CTCA followed by CCA vs CCA alone. Alternative assumptions were tested in patient scenario and sensitivity analyses. Results: CCA was found to dominate CTCA, however, CTCA was relatively more cost-effective in females, in advancing age, in patients with lower pre-test probabilities of CAD, the higher the sensitivity of CTCA and the lower the probability of undergoing a confirmatory CCA following a positive CTCA. Conclusions: Results were very sensitive to alternative patient populations and modeling assumptions. Careful consideration of patient characteristics, procedures to improve the diagnostic yield of CTCA and selective use of CCA following CTCA will impact whether CTCA is cost-effective or dominates CCA.